(untitled) (Theatrum historiae, 2010)
An interesting product of the Silesian mints in the early modern period are coins commemorating the death of successive members of the Legnica-Brzeg Piast dynasty. In this way, dukes Joachim Fryderyk (died 1602), Jerzy Rudolf (died 1653), George III (died 1664), Louis IV (died 1663), Christian (died 1672) and Jerzy Wilhelm (died 1675) were commemorated. ) and princess Anna Maria (died 1605), Zofia Elżbieta (died 1622), Zofia Katarzyna (died 1659), and Elżbieta Maria Karolina (died 1664). The posthumous coins of the Princes of Legnica and Brzeg, due to the minting technique, have the character of coins, but the purpose of their issue brings them closer to medals. The monetary nature was clearly emphasized on the numismatic items minted after the death of Zofia Katarzyna, as they have the denomination clearly indicated. On the other hand, on the posthumous numismatics of Zofia Elżbieta, we can see the information "nummus argenteus". The backs of these posthumous coins always contain information of a genealogical nature. The classification of posthumous coins presents a number of difficulties. An important factor influencing the classification of these numismatic items is their weight. Technically, these numismatic items resemble coins, but the weight and circumstances of minting encourage them to be considered medals. Posthumous coins usually weighed much more, but sometimes also clearly less than the equivalent in circulation. Hence, the definition of their denominations is purely conventional. They were not put into circulation and did not end up in circulation, as evidenced by the practical lack of these coins in monetary treasures. The link between the coins and the posthumous medals are the posthumous medals of Jerzy Wilhelm, which have a reverse almost identical in form and content to that known from posthumous coins. There is usually no clip among the posthumous coins of the Legnica and Brzeg princes. The exception is the clip of Joachim Fryderyk’s posthumous half-thaler (FS 1387, Kop. 103c) and the clips stamped with half-thalers on the occasion of the death of Anna Maria. The remnants of the non-economic role of posthumous coins, but also of the fashion that was widespread in modern times, through the use of posthumous coins to decorate costumes or chains are ears, intricate bindings and holes. Posthumous coins are an interesting supplement to the funeral ceremonies and a valuable - still sought after memento of the Piast dynasty.